Aged women‟s perception about aging with quality of life: subsidies to public interventions - Cartaxo, Hemília Gabrielly de Oliveira; Silva, Emília Amélia Pinto Costa da; Santos, Ana Raquel Mendes dos; Siqueira, Poliana Germano Bezerra de Sá; Pazzola, Clara Maia; Freita, Clara Maria Silvestre Monteiro de (Rev Rene, 2012)
The Quality of Life (QL) of elderly is quite debated nowadays. Though, this study aims to explore the perception of 37 elderly women from Máster Vida Project (Recife/PE) about their QL and to identify which of the domains and questions of QL from WHOQOL-Bref were more mentioned by them. It was used a socioeconomic and demographic form and the following open question: What does quality of life mean to you? The software AQUAD was used to conduct thematic content analysis, and the diagrams were made by the GoDiagram Express 2.0 program. The majority of participants reported that QL was associated to the environment domain, where the health, financial independence and leisure time factors were more related. We so concluded that it‟s important the attention of the health professionals, for them to make some interventions to improve the quality of life, because the presence of diseases and financial difficulties can have a bad influence in the QL.